A rare case of sialolipoma of submandibular gland - Paramasivam, Praveen K.; Sahu, Pankaj K.; Bishnoi, Tapasya; Yadav, Mukesh K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Lipomas in head and neck region are common but prevalence in salivary glands is rare with majority in parotid. Sialolipoma is a rare tumour of the salivary gland that is composed of mature adipocytes and normal salivary gland tissue. We report an extremely rare case of sialolipoma of left submandibular gland in a 39-year-old male who presented with complaints of insidious onset gradually progressive swelling in left submandibular region with no pain, discolouration or discharge. On examination, a 5×4 cm soft, non-tender swelling was noticed in (L) submandibular region. Ultrasonography of neck revealed enlarged (L) submandibular gland with hypoechoic area of 5 mm diameter and small areas of echogenic foci with no cervical lymphadenopathy. Contrast enhanced computed tomography (CECT) neck showed a 5.6×2.7×4 cm well defined fat attenuated lesion in (L) submandibular space, suggestive of lipoma with a well-defined enhancing soft tissue component within the lesion. He underwent excision of (L) submandibular gland along with fibrofatty tissue under general anaesthesia. Histopathological examination revealed submandibular gland with normal histomorphological features along with mature adipocytes in fibrofatty tissue. The patient is on regular follow-up with no recurrence.